Interactive Virtual Reality Simulation - A Tool for Improving Understanding of Safety and Environmental Risk Relating to Sustainable Mining Practices - Squelch, Andrew; Stothard, P.; Laurence, A. (The Australasian Institute of Mining and Metallurgy, 2015)
Using case studies, this extended abstract and the associated conference presentation demonstrate that novel technologies used for an application in an advanced mining economy may be leveraged by emerging economies to assist in the development of people working in their local mining industry. The conference presentation reviews the development of virtual reality (VR) simulation and its implementation in industry, discusses some potential barriers to continued development, considers new developments and discusses how human factors may limit VR simulation use in the future, especially with respect to transferring existing systems to new and developing economies. The need for continued industry- and university-level collaboration to develop a sustainable simulator technology industry that can help develop a sustainable mining industry is also discussed.